A threat from within? Perceptions of immigration in an enlarging European Union. (November 2020) - Jeannet, Anne-Marie
Scholars have taken a considerable interest in how global immigration to Europe generates public concern, but we still know little about the role that migration from within the European region has in fueling apprehensions. To better understand this, I examine how public attitudes towards immigration have responded to migration following the European Union's most extensive enlargement along its eastern border in 2004. Using recent advances in multilevel modeling, this article analyzes the longitudinal, cross-sectional relationship between east–west internal European migration on public attitudes towards the economic and cultural aspects of immigration in Western Europe using individual-level data from the European Social Survey (2004–2014). The results demonstrate that growing populations of Central and Eastern European foreigners have contributed to Western Europeans' perception of immigration as an economic threat, even when taking into account simultaneous immigration from outside Europe. Moreover, the relationship between east–west immigration and an individual's perception of immigration as a threat is conditional upon their socio-economic status. These findings underscore how within-European immigration in Western Europe has become consequential to the public's attitudes about immigration more generally.